2009
DOI: 10.1093/gerona/glp028
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic Hypotension As Cause of Syncope in Patients Older Than 65 Years Admitted to Emergency Departments for Transient Loss of Consciousness

Abstract: In patients older than 65 years, Parkinson's disease and neurological comorbidity are strictly related to OH syncope. Moreover, this study suggests the independent link between OH syncope and the use of vasoactive drugs, identifying the majority of cases as adverse drug reaction, a preventable risk factor for syncope and falls in the older population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 24 publications
3
33
1
3
Order By: Relevance
“…However, the evidence on the relative contribution of each class of medication to the development of OH remains controversial and inconclusive as mentioned previously. 4,8,14,16,18,23,24 Our study did not find any association between medication use and the presence of OH, further suggesting that the differences in hemodynamic responses between the OHN and OHP groups were more likely to be intrinsic and not attributable to any individual medications or clinical conditions.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…However, the evidence on the relative contribution of each class of medication to the development of OH remains controversial and inconclusive as mentioned previously. 4,8,14,16,18,23,24 Our study did not find any association between medication use and the presence of OH, further suggesting that the differences in hemodynamic responses between the OHN and OHP groups were more likely to be intrinsic and not attributable to any individual medications or clinical conditions.…”
Section: Discussioncontrasting
confidence: 49%
“…According to the literature, up to 28% of syncope events could have been caused by OH. 8,[17][18][19] Hence, it is possible that by excluding this elderly trauma patient population, we might have underestimated the true prevalence of OH in the trauma ward.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent falls, often experienced by OH patients, may cause hip fracture and head trauma. Meanwhile, 10% to 31% of patients presenting to emergency departments with syncope are diagnosed with OH-related syncope, [3][4][5] and OH accounts for 0.4% of all hospital admissions. 6 Although OH imposes a heavy burden in terms of medical costs, treatments for OH such as pharmacological pressor agents, elastic lower-limb stockings, and avoidance of rapid postural change remain unsatisfactory.…”
mentioning
confidence: 99%
“…Syncope can be described as a transient loss of consciousness due to transient global cerebral hypoperfusion, characterized by rapid onset, short duration, loss of tone and spontaneous complete recovery. 1 A literature search performed on definitions of syncope and related disorders found that syncope, neurocardiogenic syncope, neurally mediated syncope, orthostatic intolerance and orthostatic hypotension were defined in only 41,34,26,38 and 48% of papers, respectively, and, when definitions were given, they differed considerably between papers. 2 It is well recognized that syncope presents in a bimodal age distribution with a 3-to 4-fold rise with advancing age.…”
Section: Introductionmentioning
confidence: 99%